Diagnostics of the Financial Condition and Investment Attractiveness of Business Enterprise in the Financial Management System - BONDARUKТ.; ZAICHKO, I.; BONDARUKІ. (Scientific Bulletin of the National Academy of Statistics, Accounting and Audit, 2022)
Theoretical and methodological tools for diagnosing financial condition and its investment attractiveness of business enterprise have been deepened. The practical aspects of diagnosing the financial situation with the definition of opportunities to overcome the crisis, increase the level of investment attractiveness and the formation of future management decisions, taking into account the post-quarantine consequences. The directions of financial diagnostics of the enterprise at the expense of systematization of additional indicators for definition of financial stability of the enterprise are offered. It was found that the financial stability of the enterprise has close relationships with investment attractiveness, which indicates its impact on the results of the diagnosis of financial condition and determine the factors of building a management system of the enterprise. It is confirmed that one of the main functions of financial management in ensuring the financial stability of the enterprise is to eliminate threats that could lead to its crisis. It is shown that for the effective operation of the enterprise it is necessary to develop effective measures to increase its financial stability, liquidity, solvency, investment and business activity. The main purpose of diagnosing the financial condition of the enterprise is to assess its business activity during different periods, to identify factors that have a positive or negative impact, and to determine the real financial stability of the enterprise. In a pandemic, the diagnosis of financial condition is the initial stage of any transformation in the company, which may be associated with restructuring and restoration, change of ownership or management, assessment of creditworthiness and investment attractiveness, investment projects, business expansion and diversification, management. The methodology for diagnosing the financial condition of the enterprise is proposed to be considered as a system of successive and related stages, with the definition of goals, objectives, benchmarks and a system of indicators at each of these stages. It is determined that the optimization of financial management is not a one-time task, but a continuous and repetitive cycle of making and implementing strategic and operational decisions, which determines the continuity of the diagnostic process in the enterprise.